2014
DOI: 10.1111/joor.12228
|View full text |Cite
|
Sign up to set email alerts
|

Influence of genetic and environmental factors on oral diseases and function in aged twins

Abstract: This study was conducted to quantify the genetic and environmental contributions to oral disease and function in twins. Participants were middle-aged and old twins, 116 monozygotic and 16 dizygotic pairs whose mean age was 66·1 ± 10·3 (SD) years. Number of teeth, percentage of decayed, filled and missing teeth and periodontal status were recorded as indicators of oral disease. The widths of upper and lower dental arch served as indicators of morphological figures. Furthermore, stimulated salivary flow rate, oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…Similar results were achieved by Lovelina et al [7], who in their studies of 9 pairs of identical twins and 21 pairs of fraternal twins revealed a higher correlation of occurrence of dental caries and periodontal diseases in the case of the first group of subjects. Different results were achieved by Kurushima et al [6], probably because of the relatively higher age of patients, and as a consequence, a higher influence of the environmental component, which was defined as the main component connected with the periodontium and coexisting with genetic component -in the case of dental caries.…”
Section: Discussion Caries and Periodontal Diseasesmentioning
confidence: 93%
See 3 more Smart Citations
“…Similar results were achieved by Lovelina et al [7], who in their studies of 9 pairs of identical twins and 21 pairs of fraternal twins revealed a higher correlation of occurrence of dental caries and periodontal diseases in the case of the first group of subjects. Different results were achieved by Kurushima et al [6], probably because of the relatively higher age of patients, and as a consequence, a higher influence of the environmental component, which was defined as the main component connected with the periodontium and coexisting with genetic component -in the case of dental caries.…”
Section: Discussion Caries and Periodontal Diseasesmentioning
confidence: 93%
“…The researched works confirmed that a genetic component has an influence on the appearance of multifactoral diseases, such as teeth caries [7,8] or periodontitis [7,9]. However, they are not excluded from environmental factors, the importance of which was proved by Ooi et al [10] and Kurushima et al [6].…”
Section: Discussion Caries and Periodontal Diseasesmentioning
confidence: 98%
See 2 more Smart Citations
“…A study of self-reported periodontal disease in a Virginia twin population showed the key role of genetic factors for adult-onset periodontal disease risk (Corey et al, 1993), and oral morphology and function have been observed to be influenced by genetic components (Kurushima et al, 2015). Furthermore, data from twin studies indicate that both genetic and environmental circumstances affect periodontal disease (Michalowicz, 1994).…”
Section: Discussionmentioning
confidence: 99%